Genome‐wide association studies of alcohol dependence, DSM‐IV criterion count and individual criteria. (4th June 2019) - Lai, Dongbing; Wetherill, Leah; Bertelsen, Sarah; Carey, Caitlin E.; Kamarajan, Chella; Kapoor, Manav; Meyers, Jacquelyn L.; Anokhin, Andrey P.; Bennett, David A.; Bucholz, Kathleen K.; Chang, Katharine K.; De Jager, Philip L.; et al.
Abstract: Genome‐wide association studies (GWAS) of alcohol dependence (AD) have reliably identified variation within alcohol metabolizing genes (eg, ADH1B ) but have inconsistently located other signals, which may be partially attributable to symptom heterogeneity underlying the disorder. We conducted GWAS of DSM‐IV AD (primary analysis), DSM‐IV AD criterion count (secondary analysis), and individual dependence criteria (tertiary analysis) among 7418 (1121 families) European American (EA) individuals from the Collaborative Study on the Genetics of Alcoholism (COGA). Trans‐ancestral meta‐analyses combined these results with data from 3175 (585 families) African‐American (AA) individuals from COGA. In the EA GWAS, three loci were genome‐wide significant: rs1229984 in ADH1B for AD criterion count ( P = 4.16E−11) and Desire to cut drinking ( P = 1.21E−11); rs188227250 (chromosome 8, Drinking more than intended, P = 6.72E−09); rs1912461 (chromosome 15, Time spent drinking, P = 1.77E−08). In the trans‐ancestral meta‐analysis, rs1229984 was associated with multiple phenotypes and two additional loci were genome‐wide significant: rs61826952 (chromosome 1, DSM‐IV AD, P = 8.42E−11); rs7597960 (chromosome 2, Time spent drinking, P = 1.22E−08). Associations with rs1229984 and rs18822750 were replicated in independent datasets. Polygenic risk scores derived from the EA GWAS of AD predicted AD in two EA datasets ( P < .01; 0.61%‐1.82% of variance). Identified novel variants (ie, rs1912461, rs61826952) were associated with differential central evoked theta power (loss − gain; P = .0037) and reward‐related ventral striatum reactivity ( P = .008), respectively. This study suggests that studying individual criteria may unveil new insights into the genetic etiology of AD liability. Abstract : We performed genome‐wide association studies (GWAS) of DSM‐IV alcohol dependence (AD), AD criterion count, and individual criteria among 7418 (1121 families) European American (EA) individuals from the Collaborative Study on the Genetics of Alcoholism (COGA); and conducted trans‐ancestral meta‐analyses combined EA results with data from 3175 (585 families) African‐American individuals from COGA. Three loci in EA GWAS and three loci in meta‐analysis were genome‐wide significant with multiple phenotypes. Except the well‐known rs1229984 in ADH1B, all other findings are novel. Two findings were replicated in independent datasets. Polygenic risk scores derived from the EA AD GWAS predicted AD in two EA datasets ( P < .01). Two findings were associated with differential central evoked theta power ( P = .0037) and reward‐related ventral striatum reactivity ( P = .008), respectively.